Challenges related to the analytical process in realist evaluation and latest developments on the use of NVivo from a realist perspective. Issue 3 (3rd May 2020) - Bergeron, Dave A.; Gaboury, Isabelle
ABSTRACT: Realist evaluation (RE) is a research design increasingly used in program evaluation, that aims to explore and understand the influence of context and underlying mechanisms on intervention or program outcomes. Several methodological challenges, however, are associated with this approach. This article summarizes RE key principles and examines some documented challenges and solutions when analyzing RE data, including the development of Context-Mechanism-Outcome configurations. An analytic method using NVivo features is also presented. This method makes it possible to respond to certain analytic difficulties associated with RE by facilitating the identification of patterns and ensuring transparency in the analytical process.